RISC32-E cryptography performance evaluation - Teo, Sei Hau (2022)
This project is about performance evaluation of RISC32, RISC32-E-NQ and RISC32-E-Q for comparison purposes. The main objective of this project is to evaluate the performance of the three architectures mentioned above to have a better understanding how much RISC32-E-Q performance better than another 2 architectures in terms of cryptography operations. In this project, CoreMark is selected as the CPU benchmark due to its simplicity and conformity to the three architectures mentioned. To port CoreMark to the architectures, llvm is set up to convert the c languages source codes into RISC32 understandable machine codes. UART is also configured to obtain the desired output. In short, stimulation result are expected to be delivered at the end of the project.